Designing and validating an adaptation questionnaire among the husbands of Iranian Muslim women with breast cancer - Bigdeli Shamloo, Marzieh Beigom; Elahi, Nasrin; Asadi Zaker, Marziyeh; Zarea, Kourosh; Zareiyan, Armin (Frontiers in Public Health, 2023)
Background: Breast cancer is the most common cancer among women and is the second leading cause of cancer death. This disease affects all aspects of the patient's life and family, especially the patient's spouse, which confirms the need to adapt to these changes. The common instruments used for the investigation of adaptation among husbands of women with breast cancer are mainly outdated, one-dimensional, or non-concordant with the Iranian culture. Therefore, the present study aimed to design and validate an adaptation scale among the husbands of Iranian Muslim women suffering from breast cancer. Methods: This exploratory sequential mixed study was conducted in two qualitative and quantitative stages. In the qualitative stage, semi-structured interviews were performed with 21 participants. Then, items were developed through content analysis using the approach proposed by Elo and Kyngas on the basis of Roy's adaptation model. In the quantitative stage, the extracted items were reduced and psychometric properties such as face, content, and construct validity as well as reliability were explored. To investigate the construct validity, a cross-sectional descriptive study was conducted on 300 husbands of women with breast cancer selected via cluster sampling. Results: The initial questionnaire contained 79 items. After the assessment of face and content validity, 59 items were evaluated regarding construct validity using exploratory factor analysis. At this stage, six adaptation dimensions were observed among the women's husbands, with the variance of 51.71. The Cronbach's alpha and correlation coefficient of the questionnaire were 0.912 and 0.701, respectively. Conclusion: The developed 51-item adaptation scale had an appropriate validity and reliability and could be used for the assessment of adaptation in the target group.